Measurement of Fine-Grained Aspects of Toddler Temperament: The Early Childhood Behavior Questionnaire - Putnam, Samuel P. (Infant Behav Dev, 2006)
This article describes the development, reliability, and factor structure of a finely differentiated (18 dimensions) parent-report measure of temperament in 1.5 to 3-year-old children, using a cross-sectional sample (N = 317) and a longitudinal sample of primary (N = 104) and secondary (N = 61) caregivers. Adequate internal consistency was demonstrated for all scales and moderate inter-rater reliability was evident for most scales. Longitudinal stability correlations were primarily large over 6- and 12-month spans and moderate to large from 18 to 36 months. Factor analysis revealed a three-factor structure of Surgency/Extraversion, Negative Affectivity, and Effortful Control. In both samples and for both primary and secondary caregivers, older children received higher scores for Attention Focusing, Discomfort, Inhibitory Control, and Positive Anticipation. Primary caregivers rated females higher in Fear, and lower in High-intensity Pleasure, than males; secondary caregivers rated females higher than males in several aspects of Effortful Control.